2003
DOI: 10.1002/ddr.10165
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of carvedilol‐induced block of delayed rectifier K+ current in the NG108‐15 neuronal cell line

Abstract: The effects of the b-adrenoceptor antagonist carvedilol on delayed rectifier K + current (I K (DR) ) were examined in NG108-15 neuronal cells. Carvedilol (1-100mM) reversibly blocked I K (DR) with an IC 50 value of 5 mM. I K (DR) in response to depolarizing pulses was sensitive to inhibition by quinidine or dendrotoxin, but not by iberiotoxin, 5-hydroxydecanoate sodium, or linopiridine. The carvedilol-induced inhibition of I K (DR) could not be reversed by further application of t-butyl hydroperoxide or diazox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Previous studies have reported the importance of I K(erg) functionally expressed in pituitary cells including GH 3 cells [41,42]. Some of β-adrenoceptor blockers have been previously demonstrated to suppress HERG K + or other types of voltage-gated K + channels [13,14]. As such, we further studied the possible perturbation by BIS on this type of K + currents (i.e., I K(erg) ).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Previous studies have reported the importance of I K(erg) functionally expressed in pituitary cells including GH 3 cells [41,42]. Some of β-adrenoceptor blockers have been previously demonstrated to suppress HERG K + or other types of voltage-gated K + channels [13,14]. As such, we further studied the possible perturbation by BIS on this type of K + currents (i.e., I K(erg) ).…”
Section: Resultsmentioning
confidence: 98%
“…An earlier report showed the ability of carvedilol to suppress I K(DR) in NG108-15 neuronal cells [13]. We also explored whether or not the presence of BIS produced any effects on another types of K + currents (e.g., I K(DR) ) in these cells.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations